2019
DOI: 10.1038/s41598-019-56247-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Hippo Effectors YAP1/TAZ in Tumors of Soft Tissue and Bone

Abstract: Tumors of soft tissue and bone represent a heterogeneous group of neoplasias characterized by a wide variety of genetic aberrations. Albeit knowledge on tumorigenesis in mesenchymal tumors is continuously increasing, specific insights on altered signaling pathways as a basis for molecularly targeted therapeutic strategies are still sparse. The aim of this study was to determine the involvement of YAP1/TAZ-mediated signals in tumors of soft tissue and bone. Expression levels of YAP1 and TAZ were analyzed by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…We and others have previously shown that verteporfin can inhibit the YAP-TEAD interaction in sarcomas and suppress their growth [ 11 , 13 , 67 70 ]. In this study, we attempted to determine whether other biomarkers in the RAB6A/YAP/p53-MDM2 axis can also be therapeutically targeted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others have previously shown that verteporfin can inhibit the YAP-TEAD interaction in sarcomas and suppress their growth [ 11 , 13 , 67 70 ]. In this study, we attempted to determine whether other biomarkers in the RAB6A/YAP/p53-MDM2 axis can also be therapeutically targeted.…”
Section: Resultsmentioning
confidence: 99%
“…RABL6A has been targeted indirectly by inhibiting cyclin dependent kinases 4/6 and 2 in MPNST [ 43 ]. We and others have shown that TAZ/YAP can be targeted in sarcomas with verteporfin, which targets the TAZ/YAP-TEAD interaction [ 11 , 13 , 67 70 ]. p53 has shown the potential for therapeutic targeting [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true in STS, where immunohistochemical analysis has shown that YAP and TAZ are commonly activated (50% and 66%, respectively) across different histological types of sarcoma and correlate with increased tumor grade and decreased overall survival [43]. Isfort et al expanded upon this work by observing 486 sarcomas and reported TAZ activation in 33% and YAP activation in 53% [44]. In vitro studies show that targeting the YAP/TEAD complex with verteporfin reduces anchorage independent growth in soft agar [43] treatment with verteporfin in two different in vivo models of hepatomegaly, either induced by YAP overexpression or NF2 inactivation (negative regulator of YAP), showed considerable reduction in liver overgrowth [45].…”
Section: Hippo Pathway In Sarcoma and Role Of Verteporfinmentioning
confidence: 96%
“…The main Hippo components are differentially expressed across cancer types, such as in the cases of MST1/2 in soft tissue sarcomas [38][39][40], LATS1/2 in astrocytoma and breast cancers [41,42], TAZ in breast cancer [43,44], and MOB1 in lung and colon cancers [45,46].…”
Section: Connection With Tumorigenesismentioning
confidence: 99%